Community-Based Tourism Design to Develop a Historical Tourism Village in Yogyakarta - Wibowo, Bayu Ananto; Darsono, Darsono (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
This research was conducted in Gilangharjo Village, Yogyakarta, Indonesia, one of many potential areas in Yogyakarta to become a historical tourism village. The study is descriptive qualitative research that was conducted through four stages including observation, interview, data analysis, and research report. The data collection techniques included interviews, documentation, and recording. The literature study is taken to support the research. The results of this study are a design of a historical tourism village based on community empowerment that can be applied in the village of Gilangharjo through several ways of enhancing the human and natural resources. The project can be done by maximizing its potential, namely; (1) cultural tourism, (2) historical tourism, (3) entertainment tourism, (4) culinary tourism. It is necessary to improve the infrastructure that supports tourism in each place that can be visited. The empowerment of the Gilangharjo village community can be maximized by holding tourism village training.